Cor triatriatum dexter: A rare cause of cyanosis during neonatal period - Mohammed Hussien Alghamdi (Wolters Kluwer Medknow Publications, 2016)
Cor-triatriatum dexter is an extremely rare congenital heart defect in which there is complete persistence of the right valve of embryonic sinus venosus that results in partitioning of the right atrium into a smooth and trabeculated portion. The smooth portion receives venous blood from inferior vena cava, superior vena cava, and coronary sinus while the trabeculated portion contains the right atrial appendage and the opening of tricuspid valve. We report a 1-week-old child who presented with intermittent episodes of central cyanosis. Echocardiography, established, and bubble contrast study confirmed the diagnosis of an isolated cor-triatriatum dexter. The baby initially underwent an intervention by cardiac catheterization, which was unsuccessful in disrupting the membrane and re-direct the systemic venous flow to the right heart chambers. She subsequently had the cor-triatriatum dexter membrane resected via an uncomplicated open-heart surgery.